Context aware app recommendation using email semantic analysis - Tang, Zi Cong (2019)

(untitled)
Email is a kind of electronic tool that people used to exchange message. There are many functionalities such as spam filt ering, categories section, malicious email identification and etc are available in the email application that had been launched in the existing market. In order to increase the functionalities for the email application and further enhance the user experien ce, it is proposed to develop a recommendation system to work with the email application that provide s a recommendation based on the email content. This mean s that people can easily receive some recommendation for their next action from the email applicati on based on the email the y received. The recommendation system is planned to develop by using data mining and machine learning. The email content as the raw data and sent to the test mining to perform text classification and category the data into differen t categories. Then the da ta will go through the machine learning algorithm to perform predict and provide a recommendation that suitable for the content.